Disparity krajů ČR - Jindrová, Pavla (Univerzita Pardubice, 2009)
The Czech Republic is structured among 14 regions (NUTS3). The comparison among regions of the Czech Republic is made by clusters analysis using data of 2006. The first analysis compares 14 regions and the second analysis compares regions without the capital Prague. The results of the first analysis display dominant position of Prague and the second of Středočeský region.
Keywords: NUTS 3; disparity among regions; cluster analyses; dendrogram